2018
DOI: 10.14748/ssp.v5i2.5614
|View full text |Cite
|
Sign up to set email alerts
|

A review: Biological activity of myrtenal and some myrtenal-containing medicinal plant essential oils

Abstract: INTRODUCTION: Myrtenal, a component of many plants' essential oils, is a bicyclic monoterpenoid. Numerous effects of myrtenal in experimental animals have been found-bronchodilatory, anti-inflammatory, anti-aggregative and antihemolytic (in vitro), and antibacterial. Its other activities have been studiedantioxidant, antitumor, antihyperglycemic, vasodilating, heart rate reducing and hypotensive. Myrtenal is relatively little studied in the field of neuroscience. AIM: The aim of this article is to summarize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
(37 reference statements)
3
28
0
1
Order By: Relevance
“…Our experimental data showed that the three tested substances decreased significantly the number of contralateral rotation in apomorphine test with the best effect being observed 3 weeks post lesion for EA and decreased the number of falls/min in rotarod test with best effect for Myrt, 3 weeks after lesion. This result confirmed the reported improvement in motor coordination effect of EA and decreased the contralateral rotation effect of LA in 6-OHDA-induced neurotoxicity on a rat model of hemi-parkinsonism [87,100]. To the best of our knowledge, no studies have so far been conducted with Myrt on PD models.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our experimental data showed that the three tested substances decreased significantly the number of contralateral rotation in apomorphine test with the best effect being observed 3 weeks post lesion for EA and decreased the number of falls/min in rotarod test with best effect for Myrt, 3 weeks after lesion. This result confirmed the reported improvement in motor coordination effect of EA and decreased the contralateral rotation effect of LA in 6-OHDA-induced neurotoxicity on a rat model of hemi-parkinsonism [87,100]. To the best of our knowledge, no studies have so far been conducted with Myrt on PD models.…”
Section: Discussionsupporting
confidence: 89%
“…The ability of LA to restore DA levels was reported in 6-OHDA-and MPTP-induced models of PD [104]. In our previous studies with Sco-induced model of dementia, we have established that Myrt significantly increases DA levels in the brain [87]. The ability of the tested AOs to increase dopamine levels in the brain after the neurotoxin action (6-OHDA) provides additional strong in vivo proof-of-concept of their neuroprotective properties.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Consequently, there is growing body of literature regarding new modifications to these fascinating natural compounds and the corresponding biological and medical applications. Despite the importance of this class of compounds, there are limited reviews on the biological and pharmacological properties of monoterpene derivatives [ 1 , 2 , 3 , 4 , 5 , 6 ]. Hence, we considered it appropriate to provide a review of selected monoterpene derivatives and their diverse therapeutic activities.…”
Section: Introductionmentioning
confidence: 99%